Zakat & Sustainable Development Goals (SDGs): A Review - Nurhasanah, Neneng (Ekonomi Islam Indonesia, 2023)
This study aims to look at the development of research on "Zakat & SDGs" around the world and research plans that can be carried out based on published journals with this theme. This study used a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Zakat & SDGs" which comes from the Scopus database with a total of 39 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of research development "Zakat & SDGs" in the world. The results of the study found that in the bibliometric author mapping, the authors who published the most research on the theme "Zakat & SDGs" were Abubakar J.; Aysan AF; Ahmad S.; Siddiqui KA; Aboalsamh HM; Akmal IKB; Majid MAS; Gunawan E. Furthermore, based on the bibliometric keyword mapping, there are 4 clusters that can become research lines with topics related to Implementation of Sharia-Based Finance to Achieve SDGs, Zakat Institutions and SDGs, Sustainable Finance and Investment during the Covid-19 Pandemic and Human Development Index (HDI) and Zakat Recipients. Last, the words most used are Islamic Finance, SDGs, zakat institutions, IFI, HDI, sustainable finance & investment and Covid.